Phenotyping for waterlogging tolerance in crops: current trends and future prospects. (1st June 2022) - Langan, Patrick; Bernád, Villő; Walsh, Jason; Henchy, Joey; Khodaeiaminjan, Mortaza; Mangina, Eleni; Negrão, Sónia
Abstract : Review of waterlogging as a yield limiting stress and the benefits and challenges of applying a modern phenotyping approach to improving waterlogging tolerance of major crops. Abstract: Yield losses to waterlogging are expected to become an increasingly costly and frequent issue in some regions of the world. Despite the extensive work that has been carried out examining the molecular and physiological responses to waterlogging, phenotyping for waterlogging tolerance has proven difficult. This difficulty is largely due to the high variability of waterlogging conditions such as duration, temperature, soil type, and growth stage of the crop. In this review, we highlight use of phenotyping to assess and improve waterlogging tolerance in temperate crop species. We start by outlining the experimental methods that have been utilized to impose waterlogging stress, ranging from highly controlled conditions of hydroponic systems to large-scale screenings in the field. We also describe the phenotyping traits used to assess tolerance ranging from survival rates and visual scoring to precise photosynthetic measurements. Finally, we present an overview of the challenges faced in attempting to improve waterlogging tolerance, the trade-offs associated with phenotyping in controlled conditions, limitations of classic phenotyping methods, and future trends using plant-imaging methods. If effectively utilized to increase crop resilience to changing climates, crop phenotyping has a major role to play in global food security.